The Role of Multimodality Imaging in Left-Sided Prosthetic Valve Dysfunction - Manuela Muratori; Laura Fusini; Maria Elisabetta Mancini; Gloria Tamborini; Sarah Ghulam Ali; Paola Gripari; Marco Doldi; Antonio Frappampina; Giovanni Teruzzi; Gianluca Pontone; Piero Montorsi; Mauro Pepi (Journal of Cardiovascular Development and Disease, 2022)
Prosthetic valve (PV) dysfunction (PVD) is a complication of mechanical or biological PV. Etiologic mechanisms associated with PVD include fibrotic pannus ingrowth, thrombosis, structural valve degeneration, and endocarditis resulting in different grades of obstruction and/or regurgitation. PVD can be life threatening and often challenging to diagnose due to the similarities between the clinical presentations of different causes. Nevertheless, identifying the cause of PVD is critical to treatment administration (thrombolysis, surgery, or percutaneous procedure). In this report, we review the role of multimodality imaging in the diagnosis of PVD. Specifically, this review discusses the characteristics of advanced imaging modalities underlying the importance of an integrated approach including 2D/3D transthoracic and transesophageal echocardiography, fluoroscopy, and computed tomography. In this scenario, it is critical to understand the strengths and weaknesses of each modality according to the suspected cause of PVD. In conclusion, for patients with suspected or known PVD, this stepwise imaging approach may lead to a simplified, more rapid, accurate and specific workflow and management.